On Design and Development of Wood-Concrete Bridge Structure - Vladimir A. Utkin; Pavel N. Kobzev; Evgeny E. Basich; Victoria V. Skiba (Вестник СибАДИ, 2025)
Introduction. Timber as a structural material for bridge spans has some advantages compared to currently widespread reinforced concrete or steel. New technological and structural forms of timber spans should comply with modern requirements for load capacity and durability. Compared to foreign practice of timber bridge construction, our experience in this sphere is largely lost or does not correspond to modern conditions. The most advanced design solutions include combined timber-reinforced concrete spans.Materials and methods. The authors analyze both foreign and domestic experience of making connections in composite timber-concrete structures. The text provides information on the scope of application of timber bridges with combined logs and separately describes the design of a timber-concrete span with combined logs and the test results. Further the authors consider the experience of application of bridges with glulam girders and design solutions for the combined timber-concrete span structure. Based on the survey data for the bridges in Omsk region, the authors present the experience of bridge operation and maintenance for structures with board-nail blocks and driveway slab with a cross-laid beams. The text indicates typical damages of such spans and considers a variant of reconstructing such bridges with reinforced concrete roadway slab jointed with beams.Results. The authors identified the need to introduce new solutions to increase the durability of timber bridges. One of such solutions is the use of reinforced concrete passage slab jointed with timber beam, which also increases the overall load-bearing capacity of the span structure.Discussion and conclusions. The designs of timber-concrete spans proposed by the authors in the article have greater durability and increased load-bearing capacity compared to timber spans. This structural method can be effectively applied to the reconstruction of existing timber bridges.